PENGEMBANGAN MODUL PEMBELAJARAN IPAS MENGGUNAKAN MODEL PJBL-STEM UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN PENGUASAAN KONSEP IPAS SISWA SD - Wulan Agustina, Putri; Joko Raharjo, Tri; Arbarini, Mintarsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The 21st century education requires mastery of 4C skills, particularly critical thinking to support conceptual understanding. In IPAS learning, critical thinking is closely associated with concept mastery and meaningful knowledge application. Preliminary interviews and observations at SD Negeri Ciparay II revealed that IPAS instruction remains teacher-centered, learning modules for independent study are unavailable, and the implementation of project-based learning and STEM integration is limited, resulting in low levels of students’ critical thinking skills and concept mastery. This study aimed to develop an IPAS learning module based on Project-Based Learning integrated STEM (PjBL-STEM) and to examine its feasibility and effectiveness. This research employed a Research and Development (R&D) method using the 4D model with a one-group pretest–posttest design involving 69 students. Data were collected through interviews, observations, questionnaires, documentation, and tests. The results showed that the module was highly feasible, with feasibility percentages of 96% for the material aspect and 98% for the media aspect, and a readability score of 93%. The t-test indicated a significant improvement (p=0.000<0.05), while the average N-Gain score of 0.77 demonstrated high effectiveness. Positive responses were also reported by students (93.8%) and teachers (97.5%). Overall, the PjBL-STEM–based IPAS module was proven feasible and effective in enhancing students’ critical thinking skills and mastery of IPAS concepts, particularly in photosynthesis.